The Impact Of Reason On Faith, Ethics And Belief. - Dodson, Geran F. (Vernon series in philosophy., 2016)
The purpose of the book is to examine the theological claims of ethics, faith and belief from a philosophical perspective. The Abrahamic and Mosaic covenants of the Old Testament, Jesus of the synoptic gospels, and Paul's writings serve as the frame of reference in examining a biblical expression of reason and structured logic. The message of Jesus centered on the Kingdom of God, defined the meaning of faith and belief, established a new ethic, and framed the message in logic forms. The life and death of Jesus brought the realization of God's final covenant as prophesied by the Old Testament. H.